Antibiotic resistance and mecA characterization of coagulase-negative staphylococci isolated from three hotels in London, UK - Xu, Zhen; Mkrtchyan, Hermine V.; Cutler, Ronald R. (Frontiers in Microbiology, 2015)
Antibiotic resistance in bacteria isolated from non–healthcare environments, is a potential problem to public health. In our survey a total of 71 coagulase negative staphylococci belonging to 11 different species were isolated from 3 large hotels in London, UK. The most prevalent species was Staphylococcus haemolyticus, with S. hominis, S. warneri, S.cohnii and S. epidermidis commonly detected. Antimicrobial susceptibilities and carriage of the mecA gene were determined for all of these isolates. Most (85.9%) staphylococci were resistant to multiple antibiotics with all displaying increased susceptibility towards penicillin, fusidic acid, erythromycin and cefepime. 21 (29.5%) of the isolates were mecA positive, however MIC values to oxacillin, normally associated with the carriage of mecA, varied widely in this group (from 0.06 mg/L to 256 mg/L). 15 of the 21 mecA positive isolates carried SCCmec of these 7 were type V, 1 type I, 1 type II and 1 type IV. Additionally, five of these 15 isolates carried a previously unreported type, 1A, which involves an association between class A mec complex and ccr type 1. The remaining 6 of the 21 isolates were non-typeable and carried a combination of class A mec complex and ccrC. In addition to this, we also report on new MLST types which were assigned for 5 Staphylococcus epidermidis isolates. 4 out of these 5 isolates had MICs between 0.06 to 256 mg/L to oxacillin and would be regarded as clinically susceptible but one isolate had a high oxacillin MIC of 256 mg/L. We demonstrated widespread multiple drug resistance among different staphylococcal species isolated from non-healthcare environments highlighting the potential for these species to act as a reservoir for methicillin and other forms of drug resistance.